Analisis Daya Saing Crude Palm Oil Indonesia Ke Negara Tujuan Ekspor Pakistan dan Amerika Serikat - Lien Febrina; A. Ricco Galang Erlangga; Mutiara Az-Zahra; Raden Fadhilla Salsabila; Eka Rindah Yani; Rahul Abi Ubaidillah; Rasidin Karo Karo Sitepu; Nur Faizatul Luthfiah (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Indonesia is one of the world's largest producers and exporters of Crude Palm Oil (CPO). This study aims to analyze the competitiveness level of Indonesian CPO and the competitive position of Indonesian CPO in the target countries of the United States and Pakistan. This research uses secondary data with a time span from 2018 to 2022. The methods used in this research are the Revealed Comparative Advantage (RCA) method and Export Product Dynamic (EPD). The analysis results show that Indonesia's export competitiveness to the target countries of the United States and Pakistan is high. Then, the majority of the market share to the target countries of the United States and Pakistan is in the Rising Star position, which means there is positive growth. The government needs to synergize policies and create regulations regarding international trade agreements, the government can also simplify export licensing procedures, and Indonesian exporters need to pay more attention to the quality and composition of CPO products